The risk of miscarriage is associated with ambient temperature: evidence from coastal Bangladesh - Das, Susmita; Sagar, Sharoardy; Chowdhury, Srizan; Akter, Konok; Haq, Muhammad Zahirul; Hanifi, Syed Manzoor Ahmed (Frontiers in Public Health, 2023)
Background Exposure to high ambient temperature is reported to cause adverse pregnancy outcomes. However, considering myriad temperature and climatic conditions as well as different contextual factors, the paucity of studies from the developing regions impedes the development of a clear understanding of the heat-pregnancy outcome relationship. Materials and Methods This study was conducted in Chakaria, a coastal region of Bangladesh, where International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b) administers a health and demographic surveillance system (HDSS). The surveillance workers visit the households every three months as a part of the routine surveillance activity. Between 2012 and 2020, the surveillance workers documented histories of 23,482 pregnancies among 13,376 women and the women were followed up for their pregnancy outcomes. The temperature records were obtained from the Bangladesh Meteorological Department's weather station at Cox’s Bazar. The dates of pregnancy outcome were linked with the daily average temperature on the day of pregnancy outcome. A logistic regression model was employed to examine the relationship between temperature and the incidence of miscarriage. Results Out of 23,482 pregnancy outcomes, 3.7% were induced abortions. Among the remaining 22,624 pregnancy outcomes, 86.2% were live births, 10.7% were miscarriages and 3.1% were stillbirths. Miscarriages peaked between 8-14 weeks of gestation and varied according to temperature. For women exposed to temperatures between 28℃ and 32℃, the risk of miscarriage was 25% greater (adjusted OR 1.25, 95% CI 1.07-1.47) compared to those exposed to temperatures from 16℃ to 21℃. Conclusion The study establishes a connection between miscarriage and high ambient temperatures in a coastal region of Bangladesh. Implementing timely and appropriate adaptation strategies to prevent miscarriages is of paramount importance for a densely populated country like Bangladesh.